2017
DOI: 10.1182/bloodadvances.2017006981
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 signaling in murine bone marrow induces hematopoietic progenitor cell proliferation and aids survival from radiation

Abstract: Key Points Flagellin activates TLR5 signaling in mouse bone marrow and induces hematopoietic progenitor cell proliferation. Flagellin-induced MPP3 cells aid the survival of mice exposed to lethal irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…During steady-state normal hematopoiesis, HSCs generate functionally distinct lineage-biased multipotent progenitors (MPPs), with MPP2/3 and MPP4 populations predominantly sustaining myeloid and lymphoid lineages, respectively (Pietras et al, 2015). Stressful conditions such as infection, stress, or injury induce proinflammatory stimuli, which not only activate HSCs but also cause expansion of MPPs, in particular myeloid-biased MPP2/3 populations, thereby driving myeloid differentiation at the expense of HSC integrity (Essers et al, 2009;Pietras et al, 2016;Yamashita and Passegue, 2019;Zhang et al, 2017;Zhang et al, 2016). Consistent with the activation of proinflammatory pathways, we found that 8-12-wkold Ythdf2 CKO mice displayed expansion of HSCs and a concurrent increase in all four main subpopulations, namely MPP1-4 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During steady-state normal hematopoiesis, HSCs generate functionally distinct lineage-biased multipotent progenitors (MPPs), with MPP2/3 and MPP4 populations predominantly sustaining myeloid and lymphoid lineages, respectively (Pietras et al, 2015). Stressful conditions such as infection, stress, or injury induce proinflammatory stimuli, which not only activate HSCs but also cause expansion of MPPs, in particular myeloid-biased MPP2/3 populations, thereby driving myeloid differentiation at the expense of HSC integrity (Essers et al, 2009;Pietras et al, 2016;Yamashita and Passegue, 2019;Zhang et al, 2017;Zhang et al, 2016). Consistent with the activation of proinflammatory pathways, we found that 8-12-wkold Ythdf2 CKO mice displayed expansion of HSCs and a concurrent increase in all four main subpopulations, namely MPP1-4 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, NF-κB is the downstream of Toll-like receptors (TLRs) and mediates the radiation protection effect of several cytokines or small molecule drugs 56,57 . On the contrary, TGF-β/Smad pathway has been shown to sustain the quiescence of HSCs 21,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we observed in our experiments that Flagellin promoted MΦ differentiation in the lung, but not in blood or BM. Intraperitoneal injection of Flagellin was shown earlier to result in proliferation of myeloid-primed progenitor cells, termed MMP3 cells (Lin − Sca-1 + c-Kit + Flt-3 − CD150 − CD48 + ) ( 22 ), which are distinct from MO(D)Ps. It was not examined whether these cells expressed TLR5.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that systemic Flagellin administration drives rapid TLR5-dependent HSC cell proliferation and a great increase in multipotent progenitors. Neutrophils produced by these progenitors protected mice against total body irradiation ( 22 ). The generation of myeloid cells from hematopoietic progenitors fits in the concept of “emergency hematopoiesis.” Herein, myeloid cells are generated de novo from progenitors, to boost immune defense and tissue repair ( 23 ).…”
Section: Introductionmentioning
confidence: 99%